The Feasibility of West Sumatra Folklore as Indonesian Literature Teaching Material in High School - Yulia Fitrina; Yenni Hayati, M. Hum.; Muhardis Muhardis (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2022)
Cultural and social values that exist in Indonesia need to be taught, considering that current technological advances have an impact on the reluctance of students to learn about cultural and social values. Therefore, Indonesian language and literature teachers should be able to present learning that is integrated with cultural and social values in Indonesia. The reading texts of folklore in Indonesian teaching materials generally come from various regions in Indonesia. Judging from various folklore documentation, West Sumatra is actually rich in folklore. Each region in West Sumatra has interesting folklore and contains educational values. Of course, to be used as teaching material, there needs to be a feasibility test on these folk tales. The origin of the selected folklore texts also varies, namely the Legend of Sabai Nan Aluih from Luhak Tanah Datar, the Legend of the Origin of Lake Maninjau from Luhak Agam, the Legend of Tuanku Taram from Luhak 50 Kota, the Legend of Batu Puti from Sijunjung and Lebai Malang from the Andalas area. The respondents of this study are two teachers of Indonesian Language and Literature at the six sample schools, namely SMAN 1 Banuhampu and SMAN 2 Tilatang Kamang from Agam Regency, SMAN 1 Pariangan and SMAN 1 Batipuah from Tanah Datar Regency, and SMAN 1 Suliki and SMAN 1 Harau from District 50 Kota. The teachers were given an instrument in the form of a questionnaire consisting of five questions for each folklore. As a result, there are five indicators to determine the feasibility of West Sumatra folklore used as teaching materials, namely the language of this folklore is easy to understand, appreciative, educates characters, develops imagination, interesting, and gets a "Good" category rating.Keyword: dance, ilau, cultural homogenization